DEVELOPING FUTSAL TEST DIGITAL MEDIA IN JOGJA FIK FUTSALBY USING MACROMEDIA FLASH - Putri Agil Rakasiwi; Anita Rusyana Dewi; Rini Fitriyanti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The objectives of the research were (1) developing the product of Jogja FIKFutsal test book in the form of digital applications, and (2) creating animation andmedia containing videos for FIK Jogja Futsal tests.The implementation of this research included several stages, namely: (1) potentialand problems, (2) data collection, (3) product design, (4) design validation, (5) reviseddesign, (6) product trials, (7) product revision, (8) trial use, (9) product revision,(10) mass production.Based on the stages that have been implemented, the research produced a digitalmedia of Futsal Test FIK Jogja by using Macromedia and the specifications wereBlender with 53 109 KB file size, file type wmv duration 3 minutes 35 seconds.